2018
DOI: 10.1002/cbdv.201700409
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Endogenous β‐Glucuronidase Activity and Biologically Active Flavones‐Aglycone Contents in Hairy Roots of Baikal Skullcap

Abstract: Here, we examine the relationship between contents of principal flavones in hairy roots of Scutellaria baicalensis with the activity of the β-glucuronidase (sGUS) enzyme during a culturing cycle. Using RP-HPLC, we show that the highest contents of aglycones, baicalin and wogonin is observed at the growth days 8, 14, and 71 and reach 45, 41, and 62% (based on the total weight of hairy roots of the Baikal skullcap), correspondingly. Their accumulation is accompanied by increase of the sGUS activity, which we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…It is also interesting that the content of methylated flavones exceeded the content of unmethylated ones in the hairy roots of S. lateriflora . Previously, a similar result was obtained in a study of the hairy roots of S. baicalensis , which were also obtained in our laboratory [ 44 , 45 ]. It was suggested that a significant content of methylated flavones is a feature of the hairy roots of this skullcap species, however, the presence of wogonoside and wogonin in S. przewalskii and S. baicalensis indicated possible changes associated with the insertion of agrobacterial genes during the transformation, which is interesting and requires further study.…”
Section: Resultssupporting
confidence: 84%
“…It is also interesting that the content of methylated flavones exceeded the content of unmethylated ones in the hairy roots of S. lateriflora . Previously, a similar result was obtained in a study of the hairy roots of S. baicalensis , which were also obtained in our laboratory [ 44 , 45 ]. It was suggested that a significant content of methylated flavones is a feature of the hairy roots of this skullcap species, however, the presence of wogonoside and wogonin in S. przewalskii and S. baicalensis indicated possible changes associated with the insertion of agrobacterial genes during the transformation, which is interesting and requires further study.…”
Section: Resultssupporting
confidence: 84%
“…When the plant of S. baicalensis is affected by external stress environment, the cells will produce a large amount of H 2 O 2 ( Fu et al, 2018 ). Baicalin, a glycoside component in roots of S. baicalensis , is immediately hydrolyzed to baicalein (an aglycone component) under the action of GUS ( Dikaya et al, 2018 ; Matsuda et al, 2000 ). In this study, we revealed the dynamic change of the effects of storage time on the contents of eight active ingredients in fresh-crushed and fresh-cut roots at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon resulted in a lower baicalin content in the samples that were dried in the shade than for those that were dried in the sun. The possible explanations for this phenomenon are that baicalin is immediately hydrolyzed to baicalein by the action of the endogenous enzyme glucuronidase (GUS), which is active for a more extended period under shade drying conditions [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%